Religious Education and Ecumenical Formation in Post-confessional Settings: Essentials for the Theological Education of Pastors and Teachers of Religion - Werner, Dietrich (International journal of practical theology, 2024)
The article discusses the significance of international discourse on ecumenical formation for debates about the future of religious education in diverse environments, both from a German and global perspective. It emphasizes the historical importance of education in the ecumenical movement, tracing back to the early pioneers with a background in the World Student Christian Fellowship. The author draws from his longstanding involvement in international ecumenical work on education to advocate for ecumenical formation for students of theology, including those training to be religious education teachers. The article surveys key policy documents from German and international church bodies and concludes with six essential learnings for theological education in post-confessional environments.